Основні елементи гарантування продовольчої та екологічної безпеки України - Шкуратов, О.І. (Економіка природокористування і охорони довкілля, 2013)
Здійснено аналіз чинників сталого розвитку еколого-економічних систем сільського господарства та продовольчої безпеки. Виявлено основні елементи гарантування продовольчої й екологічної безпеки через екологізацію агропромислового виробництва. Analyzed factors of sustainable development of ecological-economic systems of agriculture and food security. On the basis of theoretical research and analysis of sustainable development of ecological-economic systems of agriculture and food security author identified the following processes and defined their relationship, which provides both sustainable development and food security through eco-safe production. The problem of providing reliable country food base through domestic production requires a shift from high-cost technology to resource saving management systems of agriculture, based on eco-safe production with their specific stimulation; improving the labor distribution between agricultural regions; the development of state-regulated food market. In the methods of state regulation of the food market should prevail measures of implementation the price and investment policies, tax relief and credits.